Analisis Faktor Eksternal yang Berkontribusi Terhadap Kinerja Studi pada Pegawai Sekretariat Daerah Kabupaten Pidie Jaya - Siagian, Alfan Dani; Iba, Zainuddin; Murni, Murni (Singkite Journal, 2023)
Assessment and analysis of ASN employee performance is an important part of evaluating work results, especially looking for causal factors. In this research we try to analyze external employee factors, namely the work environment, organizational culture and employee workload. Study of Pidie Jaya Regency Regional Secretariat Employees. With this type of associative research with statistical analysis using a path analysis model. The research results show that (1) there is a relationship between exogenous factors of the work environment, organizational culture and workload in the medium category. (2) The contribution of the three external factors is 68,3% to performance. (3) It is proven that there is a positive influence of environmental factors on employee performance by 45.16%, the influence of organizational culture on performance is 42.68%, and workload has an influence of 37.29% on the performance of the Regional Secretariat of Pidie Jaya Regency. Employee